Microalgae--novel highly efficient starch producers - Brányiková, Irena; Maršálková, Barbora; Doucha, Jiří; Brányik, Tomáš; Bišová, Kateřina; Zachleder, Vilém; Vítová, Milada (Biotechnology and bioengineering, 2011)
The freshwater alga Chlorella, a highly productive source of starch, might substitute for starch-rich terrestrial plants in bioethanol production. The cultivation conditions necessary for maximizing starch content in Chlorella biomass, generated in outdoor scale-up solar photobioreactors, are described. The most important factor that can affect the rate of starch synthesis, and its accumulation, is mean illumination resulting from a combination of biomass concentration and incident light intensity. While 8.5% DW of starch was attained at a mean light intensity of 215 µmol/(m2 s1), 40% of DW was synthesized at a mean light intensity 330 µmol/(m2 s1). Another important factor is the phase of the cell cycle. The content of starch was highest (45% of DW) prior to cell division, but during the course of division, its cellular level rapidly decreased to about 13% of DW in cells grown in light, or to about 4% in those kept in the dark during the division phase. To produce biomass with high starch content, it is necessary to suppress cell division events, but not to disturb synthesis of starch in the chloroplast. The addition of cycloheximide (1 mg/L), a specific inhibitor of cytoplasmic protein synthesis, and the effect of element limitation (nitrogen, sulfur, phosphorus) were tested. The majority of the experiments were carried out in laboratory-scale photobioreactors, where culture treatments increased starch content to up to about 60% of DW in the case of cycloheximide inhibition or sulfur limitation. When the cells were limited by phosphorus or nitrogen supply, the cellular starch content increased to 55% or 38% of DW, respectively, however, after about 20 h, growth of the cultures stopped producing starch, and the content of starch again decreased. Sulfur limited and cycloheximide-treated cells maintained a high content of starch (60% of DW) for up to 2 days. Sulfur limitation, the most appropriate treatment for scaled-up culture of starch-enriched biomass, was carried out in an outdoor pilot-scale experiment. After 120 h of growth in complete mineral medium, during which time the starch content reached around 18% of DW, sulfur limitation increased the starch content to 50% of DW.
Keywords: Microalgae; fosfor; mikrořasy; Chlorella vulgaris; Sunlight; sluneční záření; škrob; síra; Biomass; Photobioreactors; dusík; biomasa; fotobioreaktory; biotechnologie; Biotechnology; Starch; Sulfur; Phosphorus; Nitrogen